Prevalence of flukes (Fasciola hepatica and paramphistomids) in cattle in south-eastern Mexico - Hernández-Hernández J. C.; González-Garduño R.; Ortiz-Pérez D. O.; Villa-Mancera A.; Arias-Vázquez M. S.; Paz-Silva A. (Helminthologia, 2023)
The objective of this study was to determine the risk factors and prevalence of trematodes in south-eastern Mexico. The prevalence of trematodes was determined in 1010 bovines. The study was carried out from October 2018 (n=291) to December 2019 (n=719). Only in 2019 rumen and liver fluke eggs were differentiated. Faecal samples (n=311) were obtained from farms in southeast Mexico located in Tabasco, Chiapas and Campeche. In addition, the presence of flukes in liver and rumen from slaughtered cattle in abattoirs was recorded with a total of 408 samples. A logistic procedure was used to obtain the prevalence and the effect of main risk factors such as land physiography (flooded areas and hills), year, sex, animals’ age and type of sample obtained (eggs in faeces and flukes). The general prevalence of flukes in cattle was 32.3 % in 2018 and 41.7 % in 2019. Prevalence of F. hepatica (liver fluke) was 18.6 % (134/719) and that of paramphistomids (rumen fluke) was 33.4 % (240/719). The infected cattle from the slaughterhouse indicated a lower prevalence of F. hepatica (1 %) and rumen fluke (26.7 %) than in farms detected by egg in faeces (41.8 % and 42.1 %, respectively). The physiographic zone was decisive in the presence of F. hepatica and rumen fluke, while sex did not represent a risk factor (P > 0.05). The environmental conditions of the Mexican southeast favour the presence of both liver and rumen fluke.